Catalyst for air electrode, air electrode, and air secondary battery

A catalyst composed of Mn-containing perovskite oxides, heat-treated under nitrogen, addresses the suboptimal activity issue in air electrodes by improving the interaction and activity per unit amount, enhancing oxygen reduction and evolution reactions in air secondary batteries.

JP2025007055APending Publication Date: 2025-01-17NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023108209
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The activity per unit amount of catalyst in air electrodes of air secondary batteries is lower than the activity per unit amount of individual ORR and OER materials due to their composite ratio, leading to suboptimal performance.

Method used

A catalyst comprising a first oxide with a perovskite crystal structure containing Mn and a second oxide, heat-treated under a nitrogen atmosphere, is used to enhance the activity per unit amount of the catalyst.

Benefits of technology

The catalyst achieves higher activity per unit amount by optimizing the interaction between the first and second oxides, particularly through controlled volume changes and oxygen atom exchange, enhancing the oxygen reduction and evolution reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007055000001_ABST
    Figure 2025007055000001_ABST
Patent Text Reader

Abstract

To provide a catalyst for an air electrode, an air electrode, and an air secondary battery, capable of increasing the activity per unit amount of a catalyst as compared with the activity per unit amount of each material.SOLUTION: A catalyst for an air electrode contains a first oxide having a perovskite crystal structure containing Mn, and a second oxide. A value obtained by subtracting a volume of a unit lattice of the first oxide after heat treatment of the catalyst for an air electrode at 800°C under a nitrogen atmosphere from a volume of the unit lattice of the first oxide before the heat treatment is less than 0.11394 nm3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an air electrode catalyst, an air electrode, and an air secondary battery. [Background technology]

[0002] The reaction during discharge at the air electrode of an air secondary battery is the oxygen reduction reaction (ORR), and the reaction during charge is the oxygen evolution reaction (OER), so the catalyst for the air electrode is required to have high ORR and OER activity. The prior art disclosed in Patent Document 1 combines a material with high ORR activity (ORR material) and a material with high OER activity (OER material), both of which are selected from oxides with a perovskite-type crystal structure containing Mn. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-190833 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the prior art, the content of the ORR material and the OER material per catalyst is small depending on the composite ratio of the materials, so there is a problem that the activity per unit amount of the catalyst is lower than the activity per unit amount of each material.

[0005] The present invention has been made to solve this problem, and has an object to provide an air electrode catalyst, an air electrode, and an air secondary battery that can make the activity per unit amount of the catalyst higher than the activity per unit amount of each material. [Means for solving the problem]

[0006] A first aspect for achieving this object is an air electrode catalyst comprising a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide, in which the volume of the unit cell of the first oxide after heat treatment of the air electrode catalyst at 800° C. in a nitrogen atmosphere is subtracted from the volume of the unit cell of the first oxide before the heat treatment to obtain a volume of 0.11394 nm 3 Less than.

[0007] In a second embodiment, in the first embodiment, the second oxide has a Rdolphin-Popper phase.

[0008] In the third aspect, the crystal structure of the second oxide in the second aspect is represented by chemical formula A n+1 B n X 3n+1 When expressed as: the B site contains Ni.

[0009] In a fourth embodiment, in the third embodiment, the A site contains La.

[0010] A fifth aspect is any one of the first to fourth aspects, wherein the crystal structure of the first oxide is represented by the chemical formula ABO 3-δ When expressed as (δ≦0.4), the A site contains La.

[0011] A sixth embodiment is any one of the first to fifth embodiments, wherein the first oxide and the second oxide do not include an alkali metal or an alkaline earth metal.

[0012] A seventh aspect is an air electrode of an air secondary battery, comprising the air electrode catalyst according to any one of the first to sixth aspects.

[0013] An eighth aspect is an air secondary battery including the air electrode catalyst according to any one of the first to sixth aspects. Effect of the Invention

[0014] According to the present invention, the activity of the first oxide per unit amount of the catalyst can be made higher than the activity per unit amount of the first oxide. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic diagram of an air secondary battery according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Fig. 1 is a schematic diagram of an air secondary battery 10 in one embodiment. The air secondary battery 10 is a battery that uses oxygen in the air as the positive electrode active material, and includes an air electrode 11 (positive electrode) and a negative electrode 16. The air electrode 11 includes a gas diffusion layer 12 through which air (oxygen) diffuses, and a catalyst layer 14 in which an oxygen reduction reaction (ORR) occurs during discharge and an oxygen evolution reaction (OER) occurs during charge.

[0017] The gas diffusion layer 12 has a function of allowing air to pass through while preventing the intrusion of water from the outside air. The gas diffusion layer 12 is made of a sheet formed by mixing highly hydrophobic carbon such as acetylene black with a highly water-repellent polytetrafluoroethylene (PTFE) binder, a carbon mesh, a porous PTFE film, or the like. A current collector 13 is embedded in the gas diffusion layer 12. Examples of the current collector 13 include a metal mesh made of nickel or nickel-plated copper.

[0018] The catalyst layer 14 contains carbon with a high specific surface area, such as carbon black or activated carbon, a PTFE binder, and a catalyst 15 (catalyst for the air electrode). The negative electrode 16 is made of a metal containing, for example, Li, Zn, Al, Mg, Fe, etc., and has a function of generating ions in the electrolyte 18. The separator 17 electrically insulates the air electrode 11 (positive electrode) and the negative electrode 16, and also has a function of allowing the ions contained in the electrolyte 18 to pass through. The reaction in the catalyst layer 14 occurs at the three-phase interface between the solid phase (carbon and catalyst 15), the liquid phase (electrolyte 18), and the gas phase (oxygen).

[0019] The catalyst 15 includes a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide. The first oxide having a perovskite-type crystal structure is represented by the chemical formula ABO 3-δWhen expressed as (δ≦0.4), the A site contains one or more elements selected from La, Ce, Pr, and Nd, and B contains Mn. In the first oxide, a part of the elements in the A site and the B site may be replaced with one or more elements selected from transition metals such as Cr, Fe, Co, Ni, and Cu. The first oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0020] The second oxide is not particularly limited, but examples thereof include oxides having a perovskite crystal structure, particularly layered perovskite oxides having the Ruddersden-Popper phase, and oxides having a spinel crystal structure. The second oxide having a perovskite crystal structure is represented by the chemical formula ABO 3-δ When expressed as (δ≦0.4), the A site contains one or more elements selected from La, Ce, Pr, and Nd, and B contains one or more elements selected from Cr, Mn, Fe, Co, and Ni. In the second oxide, a part of the elements in the A site and the B site may be replaced with one or more elements selected from transition metals such as Cr, Fe, Co, Ni, and Cu. The second oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0021] The layered perovskite oxide with the Ruddersden-Popper phase has a layered structure in which perovskite layers ABO3 and rock salt layers AO are layered alternately. The second oxide with the Ruddersden-Popper phase is represented by the chemical formula A n+1 B n X 3n+1 In this formula, the A site contains one or more elements selected from La, Ce, Pr, and Nd, B contains one or more elements selected from Cr, Mn, Fe, Co, and Ni, and X contains O. In the second oxide, a part of the elements in the A site and the B site may be replaced with one or more elements selected from transition metals such as Cr, Fe, Co, Ni, and Cu. The second oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0022] When the second oxide having a spinel crystal structure is represented by the chemical formula AB2O4, the A site contains one or more selected from Mn, Zn, Fe, Mo, Cd, Ti, Ni, and Co, and the B site contains one or more selected from Cr, Al, Fe, Ni, Co, Mn, and V. The second oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0023] The catalyst 15 can be obtained, for example, by preparing a first oxide and a second oxide, mixing them, and heating them in a nitrogen atmosphere at 800° C. The first oxide and the second oxide can be prepared by a solid-phase method using thermal decomposition or a solid-phase reaction, a liquid-phase method such as a precipitation method or a solvent evaporation method, or a gas-phase method such as a gas-phase reaction method or an evaporation condensation method.

[0024] The particle size of the catalyst 15 is not particularly limited, but is exemplified as 2 nm to 10 μm. In order to utilize the activity of the first oxide and the activity of the second oxide, the volume ratio of the first oxide to the combined volume of the first oxide and the second oxide is preferably 20% to 80%.

[0025] The catalyst 15 may contain other elements or compounds in addition to the first oxide and the second oxide. Examples of the other elements include precious metals such as Pd, Pt, and Ag. Examples of the other compounds include oxides having a perovskite crystal structure that are different from the first oxide and the second oxide, phthalocyanine compounds, and porphyrin compounds. EXAMPLES

[0026] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0027] (Preparation of the first oxide) La(OH)3 and Mn2O3 (both of special reagent grade) were weighed out to obtain LaMnO3, and the weighed raw materials and ethanol were placed in an alumina pot together with zirconia balls, and were ground and mixed in a ball mill for 15 hours. The slurry removed from the pot was dried, then placed in an alumina crucible and fired at 1000°C. The fired powder and ethanol were placed in an alumina pot together with zirconia balls, and were ground in a ball mill for 15 hours. The slurry removed from the pot was dried, then ground in a mortar to obtain a powder (first oxide). The obtained powder was confirmed to be LaMnO3 with a perovskite-type crystal structure by powder X-ray diffraction (XRD).

[0028] (Preparation of the Second Oxide) La(OH)3 and NiO (both of special reagent grade) were weighed out to obtain La2NiO4, and the weighed raw materials and ethanol were placed in an alumina pot together with zirconia balls, and were ground and mixed in a ball mill for 15 hours. The slurry removed from the pot was dried, then placed in an alumina crucible and fired at 1000°C. The fired powder and ethanol were placed in an alumina pot together with zirconia balls, and were ground in a ball mill for 15 hours. The slurry removed from the pot was dried, then ground in a mortar to obtain a powder. The obtained powder (second oxide) was confirmed by XRD to be La2NiO4, a layered perovskite oxide with the Ruddersden-Popper phase.

[0029] (Preparation of Catalysts in the Examples) The same volumes of the first oxide and the second oxide (first oxide:second oxide = 1:1 (volume ratio)) were placed in an alumina pot together with ethanol and zirconia balls, and were ground and mixed in a ball mill for 15 hours. The slurry removed from the pot was dried and then ground in a mortar to obtain a powder. The powder was heated from room temperature to 800°C in a nitrogen atmosphere, heated at 800°C for 1 hour, and cooled from 800°C to room temperature. This produced a catalyst comprising the first oxide and the second oxide.

[0030] (Catalyst in Reference Example 1) The first oxide was used as the catalyst in Reference Example 1.

[0031] (Preparation of Catalyst in Reference Example 2) The first oxide was heated in a nitrogen atmosphere from room temperature to 800° C., heated at 800° C. for 1 hour, and cooled from 800° C. to room temperature. In this way, a catalyst in Reference Example 2 was obtained.

[0032] (Preparation of Catalyst in Reference Example 3) The first oxide and the second oxide, each having the same volume, were placed in an alumina pot together with ethanol and zirconia balls, and were mixed and ground in a ball mill for 15 hours. The slurry taken out of the pot was dried and then ground in a mortar to obtain a catalyst in Reference Example 3.

[0033] The specific surface area of ​​the catalyst in the examples and reference examples 1 to 3 was 3.5 m 2 / g to 5.0m 2 / g range.

[0034] (Preparation of ink for producing air electrodes) A 5 wt% Nafion dispersion solution (Fujifilm Wako DE521) was mixed with a KOH (0.1M) aqueous solution to prepare a 3.33 wt% Nafion dispersion solution, and then 1-propanol (Fujifilm Wako) was added to this dispersion solution to prepare a solution. Each of the catalysts in the Examples and Reference Examples 1-3 and acetylene black (Denka Li-250), which is a conductive material, were dispersed in this solution to prepare four types of ink. The ratio (mass ratio) of catalyst, conductive material, and Nafion in the ink was catalyst:conductive material:Nafion=5:1:1. The four types of inks prepared were applied to a rotating disk electrode at approximately 250 μg / cm. 2 The catalyst was then evaporated to dryness at room temperature to obtain four types of electrodes that were assumed to be air electrodes.

[0035] (Electrochemical measurements) Electrochemical measurements were performed using a rotating disk electrode apparatus (BAS RRDE-3A) to evaluate the ORR activity of the electrode (air electrode). A rotating disk electrode (RDE) was used as the working electrode, Hg / HgO (internal solution was 0.1 M KOH aqueous solution) was used as the reference electrode, and a Pt coil was used as the counter electrode in an oxygen-saturated 0.1 M KOH aqueous solution. First, cyclic voltammetry (CV) was performed using a potentiostat, and the potential was swept from 1.0 to 0.0 V relative to the reversible hydrogen electrode (RHE) at 100 mV / s for 30 cycles. Linear sweep voltammetry (LSV) was then performed, and the current was measured when the potential was swept from 1.0 to 0.0 V relative to the RHE at 10 mV / s. During the measurements, the RDE was rotated at 1600 rpm to prevent charge transfer rate limitation and the adhesion of air bubbles. From the results of the current measurements using LSV, the surface area of ​​the electrode was determined to be 0.126 cm 2 The current density is 0.4mA / cm 2 The potential was calculated at this time and the results are shown in Table 1.

[0036] [Table 1]

[0037] Since the higher the potential, the higher the ORR activity, according to Table 1, the order of highest ORR activity is Example, Reference Example 2, Reference Example 1, and Reference Example 3. It was confirmed that the ORR activity of the catalyst in the Example in which LaMnO3 and La2NiO4 were combined was higher than the ORR activity of LaMnO3 alone (Reference Examples 1 and 2).

[0038] (Volume of unit cell of LaMnO3) The LaMnO3 contained in the catalysts in the examples and reference examples 1 to 3 was identified by XRD, and the lattice constant of LaMnO3 was obtained from known reference data, and the volume of the unit lattice of LaMnO3 was calculated. The results are shown in Table 2.

[0039] [Table 2]

[0040] According to Table 2, it is clear that the volumes of the unit cells of LaMnO3 in Reference Examples 1 and 3 that were not subjected to heat treatment are equal, and that the volumes of the unit cells of LaMnO3 in the heat-treated Example and Reference Example 2 are smaller than the volumes of the unit cells of LaMnO3 in Reference Examples 1 and 3. Focusing on the heat-treated Example and Reference Example 2, it is clear that the volume of the unit cell of LaMnO3 in the Example combined with La2NiO4 is larger than the volume of the unit cell of LaMnO3 in Reference Example 2 that was heat-treated as LaMnO3 alone. The volume of the unit cell of LaMnO3 varies depending on whether or not heat treatment was performed, and since the heat treatment was performed in a nitrogen atmosphere, it was presumed that the variation in the volume of the unit cell of LaMnO3 is related to the loss of O atoms.

[0041] The value obtained by subtracting the volume of the unit lattice of LaMnO3 in Reference Example 2 from the volume of the unit lattice of LaMnO3 in Reference Example 1 (hereinafter referred to as the "reference value") is 0.11394 nm 3 The volume of the unit cell of LaMnO3 of the example combined with La2NiO4 is larger than the volume of the unit cell of LaMnO3 of Reference Example 2, which was heat-treated as LaMnO3 alone, so the value obtained by subtracting the volume of the unit cell of LaMnO3 of the example from the volume of the unit cell of LaMnO3 of Reference Example 3 was 0.11156 nm, which is smaller than the reference value. 3 It was.

[0042] It was presumed that the high ORR activity of the examples was related to the loss of O atoms, that is, the volume of the unit lattice of LaMnO3. The value obtained by subtracting the volume of the unit lattice of the first oxide of the catalyst after heat treatment from the volume of the unit lattice of LaMnO3 (first oxide) before heat treatment of the catalyst at 800°C under a nitrogen atmosphere was smaller than the reference value, which suggested that the interaction between the first oxide and La2NiO4 (second oxide) influenced the loss of O atoms of the first oxide. Therefore, it was presumed that the activity of the first oxide per unit amount of the catalyst can be made higher than the activity per unit amount of the first oxide when the value obtained by subtracting the volume of the unit lattice of the first oxide of the catalyst after heat treatment from the volume of the unit lattice of the first oxide of the catalyst before heat treatment of the catalyst at 800°C under a nitrogen atmosphere was smaller than the reference value.

[0043] In the examples, La2NiO4 composited with LaMnO3 is a layered perovskite oxide having a Rdolphin-Popper phase, and it was presumed that O atoms resulting from the loss of O atoms in LaMnO3 may have been incorporated between the layers. The catalyst in the examples is a composite of LaMnO3 (first oxide) having a perovskite-type crystal structure containing Mn and La2NiO4 (second oxide) having a perovskite-type crystal structure having a Rdolphin-Popper phase, and it was presumed that this facilitated the exchange of O atoms between the first oxide and the second oxide.

[0044] After the catalyst in the example was heat-treated again at 800°C under a nitrogen atmosphere, LaMnO3 was identified by XRD, the lattice constant of LaMnO3 was determined from known reference data, the volume of the unit cell of LaMnO3 was calculated, and the value obtained by subtracting this volume from the volume of the unit cell of LaMnO3 before the immediately preceding heat treatment was smaller than the reference value. Therefore, it was made clear that the change in the volume of the unit cell of LaMnO3 before and after the heat treatment is a characteristic of the catalyst in the example.

[0045] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.

[0046] In the embodiment, the catalyst 15 arranged in the air electrode 11 of the air secondary battery 10 has been described as an example, but this is not necessarily limited to this. It is of course possible to arrange the catalyst 15 in other air electrodes. Examples of other air electrodes include air electrodes of fuel cells and air electrodes of water electrolysis. [Explanation of symbols]

[0047] 10. Air secondary battery 11 Air electrode 15 Catalyst (air electrode catalyst)

Claims

1. A catalyst for an air electrode, comprising a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide, The volume of the unit cell of the first oxide after the heat treatment of the air electrode catalyst at 800° C. in a nitrogen atmosphere is subtracted from the volume of the unit cell of the first oxide before the heat treatment, and the difference is 0.11394 nm 3 A catalyst for the air electrode that is smaller than

2. 2. The air electrode catalyst according to claim 1, wherein the second oxide has a Rudolfden-Popper phase.

3. The crystal structure of the second oxide is represented by chemical formula A n+1 B n X 3n+1 3. The air electrode catalyst according to claim 2, wherein the B site contains Ni.

4. 4. The air catalyst according to claim 3, wherein the A site contains La.

5. The crystal structure of the first oxide is represented by the chemical formula ABO 3-δ 5. The air electrode catalyst according to claim 1, wherein the A site contains La when expressed by (δ≦0.4).

6. 5. The air electrode catalyst according to claim 1, wherein the first oxide and the second oxide do not contain an alkali metal or an alkaline earth metal.

7. An air electrode of an air secondary battery, comprising the air electrode catalyst according to claim 1 .

8. An air secondary battery comprising the air electrode catalyst according to claim 1 .

Citation Information

Patent Citations

  • Electrode for secondary battery

    JP2005190833A